American-Soviet Cultural Diplomacy : the Bolshoi Ballet's American Premiere. - McDaniel, Cadra Peterson (Lexington Books, 2014)
This book is the first full-length examination of a Soviet cultural diplomatic effort. In her work, McDaniel focuses on the key role that the Soviets assigned to the arts in transforming societies and demonstrates that the Soviets conceived of the arts as a kind of ""artful warfare""; a valuable weapon in winning the Cold War.